Analisis Pemikiran Tujuh Filsuf Islam dan Implikasinya Terhadap Pendidikan di Indonesia: Analysis of the Thoughts of Seven Islamic Philosophers and Their Implications for Education in Indonesia - Hidayanty, Nurul; Harahap, Abdul Hamid Haji; Arif, Mahmud (Jurnal Filsafat Indonesia, 2024)
This article analyzes the thoughts of seven Islamic philosophers and their implications for Islamic Education in Indonesia. This writing summarizes the thoughts of seven famous Islamic educational philosophers, such as Al-Ghazali, Ibnu Khaldu, Hasyim Asy'Ari, Ahmad Dahlan, Al-Zarnuji, Hamka, and M. Naquib Al-Attas. Next, the article explains the implications of these figures' thoughts on Islamic education in Indonesian. Theepurpose of thisswriting is toianalyze theythoughts oftthe seven Islamic philosophers and then explain their implications for Islamic education in Indonesian. The researchhmethod useddis a literature studynusing the book, “Book of Philosophy of IslamiccEducation (Philosophical Studies and Thoughts on Islamic Education)” written by Dr. H.M. Suyudi, M.Ag as primary data source. Secondary data was taken from literature related to this topic. Theediscussion in thissarticle shows thattthe educational thoughts of these seven figures have similarities in viewing general education as something that must be studied. The implications oftthe thoughts ofsIslamic philosophers for education innIndonesia include the expansion of formal madrasa education, the application of education to morals in the learning process, an emphasis on etiquette towards teachers, and curriculum concepts that are in line with contemporary thinking.